2009
DOI: 10.1074/jbc.m109.031724
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a High Affinity Peptide Inhibitor of ClC-2 Chloride Channels

Abstract: The ClC protein family includes voltage-gated chloride channels and chloride/proton exchangers. In eukaryotes, ClC proteins regulate membrane potential of excitable cells, contribute to epithelial transport, and aid in lysosomal acidification. Although structure/function studies of ClC proteins have been aided greatly by the available crystal structures of a bacterial ClC chloride/proton exchanger, the availability of useful pharmacological tools, such as peptide toxin inhibitors, has lagged far behind that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
(77 reference statements)
1
37
0
1
Order By: Relevance
“…However, methadone had no effect on forskolin-IBMX-stimulated Cl Ϫ currents in recombinant hCFTR/HEK293 cells. Recently, the peptide toxin inhibitor GaTx2 has become available (47). It does not inhibit CFTR, but it potently inhibits ClC-2 (IC 50 ϳ20 nM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, methadone had no effect on forskolin-IBMX-stimulated Cl Ϫ currents in recombinant hCFTR/HEK293 cells. Recently, the peptide toxin inhibitor GaTx2 has become available (47). It does not inhibit CFTR, but it potently inhibits ClC-2 (IC 50 ϳ20 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methadone was identified to be an inhibitor of recombinant human ClC-2 (hClC-2), but not recombinant human CFTR (hCFTR), with half-maximal inhibition (IC 50 ) at 100 nM (7), suggesting that it can be used to differentially inhibit ClC-2, but not CFTR. Interestingly, recently, a peptide toxin inhibitor, GaTx2, was identified and shown to differentiate between ClC-2 and CFTR (47). It potently, but partially, inhibited ClC-2 (IC 50 ϳ20 pM) by ϳ80% and had no effect on CFTR, even at 60 nM.…”
mentioning
confidence: 98%
“…The availability of a more potent and specific peptide inhibitor of CLCN2 (36) may improve the ability to confidently determine CLCN2 contribution over less specific inhibitors. GaTx2 is a peptide isolated from the venom of the scorpion Leiurus quinquestriatus hebraeus (Lqh) and shows no inhibitory affect on ClC-1, ClC-3, ClC-4, CFTR, GABA c , Ca 2ϩ -dependent Cl Ϫ channels, or Shaker ShB-IR K ϩ channels (36). It inhibits CLCN2 at concentrations as low as 100 pM in vitro but shows its highest rates of inhibition at 10 nM (36).…”
Section: Discussionmentioning
confidence: 99%
“…GaTx2 is a peptide isolated from the venom of the scorpion Leiurus quinquestriatus hebraeus (Lqh) and shows no inhibitory affect on ClC-1, ClC-3, ClC-4, CFTR, GABA c , Ca 2ϩ -dependent Cl Ϫ channels, or Shaker ShB-IR K ϩ channels (36). It inhibits CLCN2 at concentrations as low as 100 pM in vitro but shows its highest rates of inhibition at 10 nM (36). As expected, we found that in vivo somewhat higher concentrations were required to show pronounced inhibition (100 -400 nM, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent progress demonstrates the potential for development of novel ClC-specific compounds. Compounds specific to the ClC-2 channel and to the ClC-ec1 antiporter have recently been described (59,137). Of relevance to the kidney, Pusch and colleagues (48) have systematically characterized and developed small-molecule inhibitors and activators of the ClC-K channels.…”
Section: Clc-ka/bmentioning
confidence: 99%